Late graft failure after kidney transplantation as the consequence of late versus early events. Issue 5 (5th December 2017) - Gaston, Robert S.; Fieberg, Ann; Hunsicker, Lawrence; Kasiske, Bertram L.; Leduc, Robert; Cosio, Fernando G.; Gourishankar, Sita; Grande, Joseph; Mannon, Roslyn B.; Rush, David; Cecka, J. Michael; Connett, John; et al.
Abstract : Beyond the first posttransplant year, 3% of kidney transplants fail annually. In a prospective, multicenter cohort study, we tested the relative impact of early versus late events on risk of long‐term death‐censored graft failure (DCGF). In grafts surviving at least 90 days, early events (acute rejection [AR] and delayed graft function [DGF] before day 90) were recorded; serum creatinine (Cr) at day 90 was defined as baseline. Thereafter, a 25% rise in serum Cr or new‐onset proteinuria triggered graft biopsy (index biopsy, IBx), allowing comparison of risk of DCGF associated with early events (AR, DGF, baseline serum Cr >2.0 mg/dL) to that associated with later events (IBx). Among 3678 patients followed for 4.7 ± 1.9 years, 753 (20%) had IBx at a median of 15.3 months posttransplant. Early AR (HR = 1.77, P  < .001) and elevated Cr at Day 90 (HR = 2.56, P  < .0001) were associated with increased risk of DCGF; however, later‐onset dysfunction requiring IBx had far greater impact (HR = 13.8, P  < .0001). At 90 days, neither clinical characteristics nor early events distinguished those who subsequently did or did not undergo IBx or suffer DCGF. To improve long‐term kidney allograft survival, management paradigms should promote prompt diagnosis and treatment of both early and later events. Abstract : In 3678 kidney transplant recipients at seven North American centers, new onset of renal dysfunction or proteinuria occurring beyond 90 days posttransplant exerts substantially more influence on late graft failure than earlier events, lending support for prompt diagnosis and therapy throughout the life of an allograft.